MASALAH – MASALAH PENDIDIKAN ISLAM DALAM ERA GLOBALISASI - Deassy Arestya Saksitha; Bagus Pratama; Musthofa Husen; Rido Agustian; Sarah Salsabila; Shinta Adha Selina (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Islamic education currently faces complex challenges amidst the currents of globalization, the Society 5.0 era, and the rapid development of information technology. This study aims to analyze the impact of globalization on Islamic education, the problems of student morals and character, and the challenges of integrating information technology into learning systems. The method used is descriptive analysis with a qualitative approach through literature review. The results of the study show that globalization brings ease of information access, but on the other hand, it triggers moral degradation, individualism, and the misuse of social media that contradicts Islamic teachings. Furthermore, digital transformation in Islamic educational institutions is still constrained by limited digital competence of educators and infrastructure gaps. This research concludes that the success of Islamic education requires synergy between the government, educational institutions, educators, and parents in integrating technology wisely. Strengthening character education based on the values of the Qur'an and As-Sunnah is necessary so that students can adapt to global competition without losing their identity as Muslims.